(3QSGdI GdhGOi (B( (3QSGdI Edi OYGI GdJhMjO HGdHdO Gdejehf GdWGgQ GdhGOi (B)s - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi Gdehdi GdYGd dYdI GdYdd GdEdg GdMGce hTcQJ YHOg ef GdYHO GdebJfi HgGA GdOjf hdSGf GdeDefjf hSfO GdehMOjf s
(3BNQgG (B:s
(3Efg Ydi Pdc bOjQ hGdMeO dehdGfG hMOg hGdTcQ ddEeGe GdgGOi YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B52s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds